Synthesis of glycerol-free fatty acid methyl ester using interesterification reaction based on solid acid carbon catalyst derived from low-cost biomass wastes - Wong, W.-Y. (John Wiley and Sons Ltd, 2022)
The current research was aimed to corroborate as well as compare the feasible applicability of waste banana peel and empty fruit bunch (EFB) in synthesising high-performing heterogeneous catalysts. The solid acid catalysts originated from biomass wastes were employed for the synthesis of glycerol-free fatty acid methyl ester (FAME) using catalytic interesterification process pathway. Acetic acid was produced as the by-product instead of glycerol. The heterogeneous acid catalysts were synthesised utilising sulphuric acid through direct sulfonation with thermal treatment. The concentration of the sulphuric acid was manipulated from 2 to 13 mol Lâ1 to investigate its effects on the resulting FAME yield while maintaining the sulfonating ratio at 10 mL gâ1. The catalytic performances of the as-synthesised catalysts were studied under reaction conditions of 12 wtÂ catalyst loading, 50:1 methyl acetate to oleic acid molar ratio for a duration of 8 hours at 60Â°C. The catalyst produced by activated carbon derived from EFB and sulfonated with 13 mol Lâ1 sulphuric acid exhibited the highest FAME yield at 44.3. The parameter studies on reactant ratio (45:1-70:1), reaction temperature (90Â°C-130Â°C) and time (4-24 hours) of interesterification reaction discovered a general increasing trend in the FAME yield up to 52.3 with the optimum conditions of 50:1, 110Â°C and 8 hours, respectively. The catalyst was recyclable with 82 of the catalytic performance retained after five successive cycles with catalyst reactivation. This study confirmed that the renewable heterogeneous catalyst derived from biomass waste could catalyse the glycerol-free interesterification process via an environmentally benign and promising approach for green fuel production. Â© 2020 John Wiley & Sons Ltd.